2007
DOI: 10.1590/s1517-83822007000300001
|View full text |Cite
|
Sign up to set email alerts
|

The use of standard methodology for determination of antifungal activity of natural products against medical yeasts Candida sp and Cryptococcus sp

Abstract: Methodology for testing natural compounds for determination of antifungal activity had been developed with adaptations. The most used are bioautography and agar diffusion with a complex and no defined media. In this study, different methods for determination of antifungal activity of natural products are discussed and the use of M27-A2 microdilution test from CLSI (Clinical and Laboratory Standards Institute, 2002), as general standard methodology for testing plant extracts activity is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 53 publications
0
98
1
11
Order By: Relevance
“…Spores of the mold were harvested into sterile distilled water from monoconidial cultures, developed on potato dextrose at 24°C during 7 days. The minimum inhibitory concentrations (MICs) of the extracts were determined against all the tested microorganisms using the broth microdilution method (Scorzoni et al, 2007). Microbial samples were prepared by dilution with growth media to obtain inocula at 10 5 colony forming units (CFU) per mL culture.…”
Section: Extract Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…Spores of the mold were harvested into sterile distilled water from monoconidial cultures, developed on potato dextrose at 24°C during 7 days. The minimum inhibitory concentrations (MICs) of the extracts were determined against all the tested microorganisms using the broth microdilution method (Scorzoni et al, 2007). Microbial samples were prepared by dilution with growth media to obtain inocula at 10 5 colony forming units (CFU) per mL culture.…”
Section: Extract Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…Em busca de obter resultados mais seguros, utilizou-se a técnica de microdiluição em caldo (orientado pelo NCCLS), oferecendo uma maior confiabilidade ao estudo em virtude do método apresentar vantagens como sensibilidade e quantidade mínima de reagentes, o que facilita um maior número de réplicas. No método da microdiluição as substâncias são solubilizadas, ocorrendo um maior contato do óleo com as célu-las bacterianas, o que torna o método mais sensível para a determinação da CIM, minimizando a inconsistência dos resultados (SCORZONI et al, 2007). A utilização do controle positivo (diclugonato de clorexidina), controle de crescimento e de controle de esterilidade colabora para redução do viés metodológico, proporcionando uma maior confiabilidade nos resultados apresentados (CASTRO, LIMA, 2010).…”
Section: Discussionunclassified
“…Several Fabaceae species have been evaluated for their antifungal properties (Scorzoni et al, 2007) among them Pterogyne nitens Tul., Fabaceae, a typical leguminous plant from Brazilian flora has been studied for antimicrobial activity. Previous biological studies have demonstrated that extracts from the barks of P. nitens did not show antibacterial activity (Salvat et al, 2001).…”
Section: Discussionmentioning
confidence: 99%